Empowering pink october: a triumph in breast cancer awareness at AEON Rawang - Ramli Hamid, Marlina Tanty; Abdul Hamid, Shamsiah; Ab Mumin, Nazimah; Abdul Rashid, Nor Faezan; Hussainy Hasbullah, Harissa; Arbain, Nurzatul Azmira (Faculty of Medicine, 2023)
The primary objective of this community engagement programme was to instill awareness and encourage early detection through mammography screening at Hospital Al-Sultan Abdullah UiTM (HASA) during the pivotal month of October. Our overarching aim was to ensure breast cancer is detected early to receive the optimal treatment, thereby enhancing survivorship rates.